2007
DOI: 10.1039/b615661d
|View full text |Cite
|
Sign up to set email alerts
|

Length exclusion in the adsorption of chain molecules on chabazite type zeolites

Abstract: In the adsorption of linear C1-C8 alkanes, alkenes and alcohols on zeolite chabazite, molecules smaller than 6.7 A are adsorbed in significant amounts, whereas longer chains are almost fully excluded from the micropores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
30
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 11 publications
10
30
1
Order By: Relevance
“…It is generally accepted that the 0.38 nm apertures of CHAtype molecular sieves are small enough to categorically exclude methylalkanes from the interior surface [86]. Recent experimental studies corroborate molecular simulations indicating that CHA-type molecular sieves also contain too many of these narrow apertures per n-alkane to afford the complete adsorption of n-octane or n-decane [16,17,53,87], so that the conversion of n-octane and n-decane is indeed likely to be limited to the exterior surface and should afford an example of pore mouth and key-lock catalysis. In agreement with catalysis occurring exclusively at the small exterior surface of CHA-type molecular sieves, CHA-type sieves exhibit a dramatically lower n-octane and n-decane conversion activity than sieves with apertures large enough to accommodate reactants and products fully at their large interior surface [88][89][90].…”
Section: Catalysis On Ton-and Mtt-type Zeolites With Inactivated Extesupporting
confidence: 55%
See 1 more Smart Citation
“…It is generally accepted that the 0.38 nm apertures of CHAtype molecular sieves are small enough to categorically exclude methylalkanes from the interior surface [86]. Recent experimental studies corroborate molecular simulations indicating that CHA-type molecular sieves also contain too many of these narrow apertures per n-alkane to afford the complete adsorption of n-octane or n-decane [16,17,53,87], so that the conversion of n-octane and n-decane is indeed likely to be limited to the exterior surface and should afford an example of pore mouth and key-lock catalysis. In agreement with catalysis occurring exclusively at the small exterior surface of CHA-type molecular sieves, CHA-type sieves exhibit a dramatically lower n-octane and n-decane conversion activity than sieves with apertures large enough to accommodate reactants and products fully at their large interior surface [88][89][90].…”
Section: Catalysis On Ton-and Mtt-type Zeolites With Inactivated Extesupporting
confidence: 55%
“…If molecular sieves with ∼0.4-nm-diameter tubular channels instead of cage-containing topologies are preferred, then ATNtype sieves should be of interest [92]. It may be too early to evaluate the potential for processing alkane shape selectively at the exterior surface of zeolites, but the external zeolite surface clearly has the potential to expand the utility of concepts associated with shape-selective external surface catalysis, including cage effects [16,53], nest effects [93], pore mouth and key-lock catalysis [4][5][6][7][8][9][10][11]13,14], length-selective cracking [54], and length exclusion [87].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Daems et al. found that shorter alcohols such as ethanol, which can adsorb with their main carbon chain perpendicularly to the length axis of the cage, are much more efficiently packed than longer alcohols, resulting in an entropic advantage and greater affinity for the shorter chains . The combination of these kinetic and entropic effects results in a strong and unusual preference for ethanol over butanol on Si‐CHA.…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, water adsorption experiments on Si‐LTA (or ITQ‐29), the pure‐silica analogue of zeolite A developed by Corma and co‐workers, indicated a very hydrophobic character with a water capacity of only 1 wt % (or 0.55 mmol g −1 ) at 20 mbar. The CHA zeolite topology on the other hand shows very specific and unusual selectivity for short chain molecules, which makes it an interesting material for the separation of short alcohols. A Si‐CHA sample, prepared by Miyamoto et al., showed hydrophobic behavior and revealed a water uptake of about 3.1 mmol g −1 at 67 mbar ( P / P 0 =0.9).…”
Section: Introductionmentioning
confidence: 99%
“…and/or [MO 6 ] (M=V, Mn, Mo, etc.) units can be controlled 1e,ln. In contrast, the pore sizes of MOFs, which are constructed from coordinatively bonded metal ions and organic ligands, can be controlled by the lengths and functional groups of organic ligands 1j,k.…”
mentioning
confidence: 99%